Molecular phylogenetic identification of the giant freshwater softshell turtle in the Hoan Kiem lake, Hanoi, Vietnam - Viet Thanh, Tran Thi; Long, Phan Ke; Minh, Nguyen Trung; Tam, Nguyen Minh (Academia Journal of Biology, 2017)
To clarify the taxonomic status of the giant freshwater softshell turtle in the Hoan Kiem Lake (2016), we analyzed four genes COI, COII, Cytb and ND4. Genomic DNA was extracted from the nail tissue. The nucleotide sequences of the four genes were determined with 652bp, 621bp, 993bp and 731bp, respectively and used to analysis of genetic relationships, together with similar sequences published on GenBank belonging to Rafetus swinhoei, Rafetus eupharaticus and Polychelys cantorii. The analysis indicated very low levels of the K2P divergence were found in all the four genes between the turtle species at Hoan Kiem Lake and R. swinhoei (0-3.7%), while very high levels of divergence were observed between the turtle species at Hoan Kiem Lake and R. eupharaticus (8.6-12.8%), and P. cantorii (14.9-25.4%). Phylogenetic analysis showed that the turtle species at Hoan Kiem Lake together with R. swinhoei to form a cluster with strong bootstrap value 100%. The results showed that the turtle species at Hoan Kiem Lake was R. swinhoei.